Antecedents to Merger Viewed from Company Performance in The Merger Process - Ayu Komala Dewi; Yoyo Arifardhani; Dedi Irawan (Pusat Publikasi Nusantara, 2023)
Merger is one way that can be done by State-Owned Enterprises (BUMN) to achieve business growth. Mergers of state-owned companies will have a major impact on the national economy because state-owned companies have an important role in supporting national development. This article aims to conduct a legal analysis regarding the merger of two companies under the control of the Indonesian Ministry of State-Owned Enterprises (Ministry of BUMN). This study took a sample of the business combinations that were carried out between the Perum DAMRI and the Djakarta Transportation Company (Perum PPD). The analysis carried out is from the legal and taxation aspects by considering the company's post-merger financial performance. The research found that referring to the applicable regulations, the merger of two state-owned companies will have several implications that must be mitigated by the post-merger companies.